(untitled) (Vietnam Journal of Community Medicine, 2025)
Introduction: β-Thalassemia is a common genetic disorder characterized by anemia resulting from impaired hemoglobin synthesis. The condition imposes a considerable economic burden on both patients and their families. This study aimed to analyze the cost structure and determine the factors influencing the direct treatment costs of β-Thalassemia at the Institute of Hematology and Blood Transfusion in 2024. Materials and methods: A cross-sectional descriptive study was conducted on 1,379 treatment sessions from 120 patients at the Thalassemia Center between January 2024 and December 2024. Results: The average annual direct medical cost per patient for treating β-Thalassemia was 44,811,421 VND. The largest cost components were laboratory tests, blood transfusions, and iron chelation therapy. Factors affecting the direct medical costs included the patients’ age, disease severity, and the number of treatment sessions. Conclusion: The majority of the direct medical expenses for treating β-Thalassemia were covered by the Health Insurance Fund, with laboratory tests, blood transfusions, and iron chelation therapy constituting the predominant share. Implementing strategies that ensure timely treatment adherence, effective monitoring of disease progression, and a reduction in the risk of worsening severity and complications is imperative for optimal management. Exploring further, you might consider discussing potential cost-reduction interventions, such as integrated care models or patient education programs, as well as analyzing long-term outcomes associated with preventive strategies in β-Thalassemia management.